Deciphering bacterial mechanisms of root colonization - Knights, HE; Jorrin, B; Haskett, TL; Poole, PS (Wiley, 2021)
Bacterial colonization of the rhizosphere is critical for the establishment of plant–bacteria interactions that represent a key determinant of plant health and productivity. Plants influence bacterial colonization primarily through modulating the composition of their root exudates and mounting an innate immune response. The outcome is a horizontal filtering of bacteria from the surrounding soil, resulting in a gradient of reduced bacterial diversity coupled with a higher degree of bacterial specialization towards the root. Bacteria–bacteria interactions (BBIs) are also prevalent in the rhizosphere, influencing bacterial persistence and root colonization through metabolic exchanges, secretion of antimicrobial compounds and other processes. Traditionally, bacterial colonization has been examined under sterile laboratory conditions that mitigate the influence of BBIs. Using simplified synthetic bacterial communities combined with microfluidic imaging platforms and transposon mutagenesis screening approaches, we are now able to begin unravelling the molecular mechanisms at play during the early stages of root colonization. This review explores the current state of knowledge regarding bacterial root colonization and identifies key tools for future exploration.